Analisis Sistem Informasi Akuntansi dalam Penerimaan dan Pengeluaran Kas Pada Dana Bantuan Operasional Sekolah (BOS) - Riski Hidayat, Simanjuntak; Nurbaiti; Nurwani (Ali Institute of Research and Publication, 2024)
This research aims to determine the accounting information system for cash receipts and disbursements in operational assistance funds (BOS). To find out about the management and implementation at SDN 019 Bonan Dolok. It is in accordance with the regulations implemented. This research uses a qualitative descriptive approach with data collection techniques in the form of observation, interviews and documentation directly with related parties. The subject of this research was the 019 Bonan Dolok State Elementary School, and those interviewed were the school principal, treasurer and secretary. The object of this research was the BOS fund report at 019 Bonan Dolok Elementary School. The data analysis technique used in this research uses three methods, namely data collection, data reduction and data presentation. The results of the research show that the accounting information system for cash receipts and disbursements of BOS funds is quite good, and the management of BOS funds is also quite good, starting from planning, use, implementation and accountability. Then the implementation of the accounting information system in cash receipts and disbursements of BOS funds has also been implemented well by the school.